BAHASA FIGURATIF DAN CITRAAN DALAM KUMPULAN PUISI PELABUHAN MERAH PILIHAN RIAU POS 2015 - Puspara Desi; Hasnah Faizah AR; Hadi Rumadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT: This study titled Figurative Language AndCiraan in Riau Pos options Poems 2015. This study aims to find the figurative language and imagery in the Red Ports options Poems Riau Pos, 2015. The study used to assess options Poems Riau Pos Red Port 2015 is the stilistika study. This type of research is qualitative descriptive. The object of this study is figurative language and imagery. The data source is the object of this study is a poetry text contained in a collection of selected poems Riau collection of poems, 2015. post also gets boon sagang in 2015 that in EDITORI by Zaini poet Marhalim Riau thinking about the many achievements in the field of literature. Poetry collection was first published by PT. SagangIntermedia, PekanbaruGraha Pena, Jl. SoebrantasPanam Km 10.5 Pekanbaru in Riau, the first printing of October, 2015. This collection of poems has 223 pages with 74 authors and 148 titles. To obtain the data of the study authors do observation techniques in the literature data that indicated sentence containing figurative language and imagery. The results of this study are as follows. (1) The use of figurative language found in the Red Ports options Poems Riau Pos 2015 is a comparison of figurative language (simile), hyperbole, and personification. Figurative language that dominates is the figurative language comparison (simile). The specificity of the figurative language of metaphors used by each author lies in the use of words that come from the environment, and the words derived from the author's experience of life; (2) The use of imagery in the Red Piers Poems Riau Pos options in 2015 found five types of images, the visual imagery, imagery auditory, olfactory imagery, motion imagery. Imagery that dominates in Port Mearh Poems Riau Pos options 2015 are auditory imagery. The specificity of the language of images used by the poet lies in the use of words derived from nature about the religious and socio-cultural dimensions.Keywords: Figurative Language, The images, Poetry